1989
DOI: 10.1051/rnd:19890302
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the effect of different ionophore antibiotics and of certain derivatives on rumen fermentation and on protein nitrogen degradation

Abstract: Summary -An in vitro study was carried out to evaluate the effect of different ionophore antibiotics and some of their derivatives on rumen fermentation and on the degradation of peanut meal nitrogen. The increase in the production of propionic acid at the expense of acetic acid, observed with lonomycin, nigericin, cationomycin and lysocellin, was identical to that noted with monensin. The decrease in methanogenesis observed in the presence of monensin was also found with cationomycin and lysocellin. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Characterization of in vitro fermentations in the batch-type fermenter described by Jouany and Thivend (1986) for 6 h or in Rusitec, sometimes indicated that cationomycin and lasalocid did not alter methane production whether the rumen contents were adapted to the ionophore (Bogaert et al 1989a) or not (Gaboyard 1987;Hillaire et al 1989 …”
Section: Discussionmentioning
confidence: 99%
“…Characterization of in vitro fermentations in the batch-type fermenter described by Jouany and Thivend (1986) for 6 h or in Rusitec, sometimes indicated that cationomycin and lasalocid did not alter methane production whether the rumen contents were adapted to the ionophore (Bogaert et al 1989a) or not (Gaboyard 1987;Hillaire et al 1989 …”
Section: Discussionmentioning
confidence: 99%
“…Increased molar proportions of isovalerate with addition of monensin to the SBM diet (P*M interaction, P<.001) were also observed. Molar proportions of isobutyrate and isovalerate have been reported to be decreased by ionophore (Russell and Martin, 1984;Hillaire et al, 1989;Clary et a!., 1993;Ali HaTmoud et al, 1995). The effect of ionophore on branched-chain VFA is related to its effects on ruminal feed N degradation.…”
Section: Chapter 4 Results and Discussionmentioning
confidence: 99%